Pengaruh Solvabilitas, Profitabilitas, Dividend Payout Ratio, dan Kepemilikan Manajerial Terhadap Pertumbuhan Laba (Studi Pada Perusahaan Indeks LQ45 Di Indonesia) - Putri, Vira Auliya; Purwatiningsih, Anggraeni; Suprayitno, Adi (PT. Intelek Cendikiawan Nusantara, 2025)
This study aims to analyze the effect of Solvency, Profitability, Dividend Payout Ratio, and Managerial Ownership on Profit Growth of LQ45 Index companies in Indonesia. Using a quantitative approach, the study sampled 80 data from 45 companies during the 2020-2023 period, obtained through purposive sampling. The data analysis techniques used include Descriptive Statistics, Classical Assumption Test, Multiple Linear Regression, F Test, Coefficient of Determination Test, and t Test, with data processed using SPSS software. The results show that Profitability has a negative and significant effect on Profit Growth, while Solvency, Dividend Payout Ratio, and Managerial Ownership have a negative but not significant effect on Profit Growth. Simultaneously, these factors contribute 13,4% to Profit Growth, while the remaining impact comes from other factors.